THE CORELATION BETWEEN PARENTAL COMMUNICATION ABOUT MENSTRUATIONAL AND PERSONAL HYGIENE BEHAVIOR OF ADOLESCENT GIRLS AT JUNIOR HIGH SCHOOL 1 KALIANDA - Irvani, Nava Santia; Agil, Hilda Meriyandah; Gea, Nurti Y.K (Jurnal Medicare, 2023)
Personal hygiene behavior for young women is something that needs to be considered, considering that poor personal hygiene can lead to reproductive health problems such as excessive vaginal discharge, the factors that influence personal hygiene behavior, namely parental communicationteenage girl.parent-child communication can determine how likely the child is to have good personal hygiene behavior during menstruation. The lower the communication, the more likely the child is to take personal hygiene actions that are wrong. The task of parents is to direct, provide information, and help children to avoid the possibility of making wrong decisions that will be bad for them. The design in this study is analytic with a cross sectional research design. The sampling technique used in this research is using purposive sampling technique, the number of samples is 140 respondents. Based on the results of the Chi Square statistical test output, the P-Value value (0.000) < value (0.05), this indicates that Ha is accepted... Thus, it can be interpreted that there is a relationship between parental communication about menstruation and personal hygiene behavior for adolescent girls at SMP N 1 Kalianda